Fiber-coupled superconducting nanowire single-photon detectors integrated with a bandpass filter on the fiber end-face. (14th February 2018) - Zhang, W J; Yang, X Y; Li, H; You, L X; Lv, C L; Zhang, L; Zhang, C J; Liu, X Y; Wang, Z; Xie, X M
Abstract: Superconducting nanowire single-photon detectors (SNSPDs) with both high system detection efficiency (SDE) and low dark count rate (DCR) play significant roles in quantum information processes and various applications. The background dark counts of SNSPDs originate from the room temperature blackbody radiation coupled to the device via a fiber. Therefore, a bandpass filter (BPF) operated at low temperature with minimal insert loss is necessary to suppress the background DCR. Herein, a low-loss BPF integrated on a single-mode fiber end-face was designed, fabricated and verified for the low temperature implement. The fiber end-face BPF was featured with a typical passband width about 40 nm in the 1550 nm telecom band and a peak transmittance of over 0.98. SNSPD with high SDE fabricated on a distributed Bragg reflector was coupled to the BPF. The device with such a BPF showed an SDE of 80% at a DCR of 0.5 Hz, measured at 2.1 K. Compared the same device without a BPF, the DCR was reduced by over 13 dB with an SDE decrease of <3%.